Building livelihoods for rural youth: A gendered perspective - Heckert, Jessica; Pereira, Audrey; Doss, Cheryl; Myers, Emily; Quisumbing, Agnes R. (International Food Policy Research Institute, 2019)
Young women and men in rural Africa are coming of age in rapidly changing local and global environments (National Research Council and Institute of Medicine 2005). Across the continent, countries are experiencing structural transformation (ST) as economies shift from labor-intensive and low-productivity activities, such as agriculture, to more productive and skill-intensive ones, such as manufacturing and services. Rural transformation (RT) is also under way in many countries, as rural economies, communities, and social institutions diversify (de Vries, Timmer, and de Vries 2015). Some countries are experiencing the demographic transition, as lags between declines in mortality and fertility rates have led to large youth cohorts (Bloom, Canning, and Sevilla 2003). Against this backdrop, the transition to adulthood has also changed. Compared with their parents, young people are staying in school longer, marrying later, and building their livelihoods from a broader range of economic sectors (Behrman and Sengupta 2005).